Athletic Academic Counseling: A Survey of Members of the National Association of Academic Advisors for Athletics - Serrano, Alejandro (My University, 1987)
The National Association of Academic Advisors for Athletics (NAAAA) has experienced rapid growth since its creation in 1976. In the past two years the association has doubled its membership. Presently there are 240 members (Monhagan, 1985). In an attempt to keep up with this fast growth and because of the youth of this organization of professionals, the need for research and investigation is imperative. The purpose of the survey was to identify trends and changes in the field of athletic academic counseling over the association's 10 years of existence. The author surveyed 112 advisors on 29 items. Findings showed there were more male counselors than females, males earned higher salaries, just over half had masters degrees, and that more than half of respondents did not see athletic advising as a permanent career.
Keywords: academic support; N4A; demographics